Diagnosing Recurrent DVT of the Leg by Two Different Non–Contrast-Enhanced Magnetic Resonance Direct Thrombus Imaging Techniques: A Pilot Study - Dronkers, Charlotte E. A.; Klok, Frederikus A.; van Langevelde, Kirsten; Šrámek, Alexandr; van Haren, Guido R.; Huisman, Menno V.; de Roos, Albert; Kroft, Lucia J. M. (TH Open, 2019)
Introduction Magnetic resonance direct thrombus imaging (MRDTI) is a promising technique to improve the diagnostic management of patients with a suspected ipsilateral recurrent deep vein thrombosis (DVT) by direct visualization of a thrombus. Another magnetic resonance imaging (MRI) technique, T1-weighted turbo spin-echo spectral attenuated inversion recovery (TSE-SPAIR), has the potential to image a thrombus directly with a high spatial resolution as well. The main aim of this pilot study was to investigate if adding the TSE-SPAIR sequence to an MRDTI sequence performed in patients with suspected recurrent DVT may increase the diagnostic confidence of expert MRDTI readers.Methods Fifteen patients with suspected acute recurrent DVT were included in this study. The TSE-SPAIR sequence was scanned directly after the MRDTI scan but not used to guide clinical decision making, and both scans were adjudicated post hoc two times separately by three independent expert MRDTI readers. Diagnostic confidence was scored on a 4-point Likert scale: (1) poor (definite diagnosis impossible), (2) fair (evaluation of major findings possible), (3) good (definite diagnosis possible), and (4) excellent (exact diagnosis possible).Results The diagnostic confidence of expert readers increased when adding the TSE-SPAIR sequence on top of the MRDTI sequence from “good” (median, 3.0; interquartile range [IQR], 2.66–3.0) to “excellent” (median, 3.67; IQR 3.33–3.67; p = 0.001). Evaluation of the scans in the reversed order 5 months after initial reading showed similar results. Diagnostic accuracy for proximal DVT of both scan techniques was good.Conclusion The extra TSE-SPAIR sequence may help increase diagnostic confidence of radiologists in cases of uncertain diagnosis in patients with suspected ipsilateral recurrent DVT.
Keywords: magnetic resonance imaging; venous thrombosis; diagnosis